UJI EFEKTIVITAS ANTIDIABETES KOMBINASI EKSTRAK DAUN MENIRAN (Phyllanthus niruri L.) Dan KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) PADA TIKUS JANTAN PUTIH - Herviani Sari; Vera Estefania Kaban; Friska Raulina Situmorang; Firdaus Fahdi (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2019)
Purpose: To determine the effect of decreasing blood glucose levels in white rats using a combination of meniran and rosella compared to glibenclamide. Method: This research was carried out experimentally. Simplicia of meniran leaves and rosella macerated using 80% ethanol. The research used 21 rats that were induced by alloxan and divided into 7 groups and all compared using glibenclamide.Group 1 (negative control) CMC Na 1%, group 2 (positive control) glibenclamide dose 0.45 mg/kgMB, group 3 single roselle extract dose 130 mg/kgMB, group 4 single meniran leaf extract dose 200 mg/kgMB, group 5 combination of meniran leaf extract dose of 100 mg/kgMB and rosella extract dose of 65 mg/kgMB, group 6 combination of meniran leaf extract dose of 200 mg/kgMB and rosella extract dose of 130 mg/kgMB, and group 7 meniran leaf extract combination dose 400 mg/kgMB and rosella extract dose 195 mg/kgMB. Result: The results showed that rats had hyperglycemia after being induced by alloxan.Data were analyzed using one way ANOVA method followed by LSD and tukeys' B post hoct test. Having a difference in the decrease in blood glucose levels between the positive control group and the five doses of meniran extract and rosella gave a significant effect compared to the negative control group did not have a significant effect in reducing blood glucose levels. Conclusion: Single meniran extract and high-dose combination extract are more effective than glibenclamide.